Comparison of Sequencing by Hybridization and Cycle Sequencing for Genotyping of Human Immunodeficiency Virus Type 1 Reverse Transcriptase - Hanna, George J. (American Society for Microbiology, 2000)
The performances of two methods of nucleotide sequencing were compared for the detection of drug resistance mutations in human immunodeficiency virus type 1 reverse transcriptase (RT) in viruses isolated from highly RT inhibitor-experienced individuals. Of 11,677 amino acids deduced from population PCR products by both cycle sequencing and sequencing by hybridization to high-density arrays of oligonucleotide probes, 97.4% were concordant by both methods, 0.8% were discordant, and 1.7% had an ambiguous determination by at least one method. A higher rate of discordance (3.9%) was observed among RT inhibitor resistance-associated codons. In 45% of the isolates, RT codon 67 was deduced as the wild-type Asp by hybridization sequencing but as the zidovudine resistance-associated Asn by cycle sequencing. In other resistance-associated codon discordances, cycle sequencing also more commonly called a known resistance-associated amino acid than hybridization sequencing did. The nucleotide sequence in the vicinity of several codons with discordant calls influenced population-based hybridization sequencing. For isolates evaluated by additional sequencing of molecular clones of PCR products by both methods, the discordance between methods was less frequent (0.4% of all 5,994 amino acids and 0 of 494 drug resistance-associated codons). At positions which were discordant or ambiguous in the population sequences, the results of sequencing of clones by both methods were usually in agreement with the population cycle sequencing result. In summary, most RT codons were highly concordant by both methods of population-based sequencing, with discordances due in large part to genetic mixtures within or adjacent to discordant codons.